Genetic variability in the serotoninergic system and age of onset in anorexia nervosa and obsessive-compulsive disorder. (January 2019) - Plana, Maria Teresa; Torres, Teresa; Rodríguez, Natalia; Boloc, Daniel; Gassó, Patricia; Moreno, Elena; Lafuente, Amalia; Castro-Fornieles, Josefina; Mas, Sergi; Lazaro, Luisa
Highlights: The age of onset of psychiatric disorders may have etiopathogenic and clinical effects. The study of genetic pleiotropy in diseases that exhibit significant co-heritability. Associating two SNPs of the HTR2A with the very-early onset phenotype in AN and OCD. Common genetic background in AN and OCD affects common aspects of the two diseases such as very-early onset. Abstract: The age of onset of some psychiatric disorders may have etiopathogenic and clinical effects and may influence outcome. Following on from previous work by our group where we showed that early onset anorexia nervosa (AN) and obsessive-compulsive disorder (OCD) shared a common genetic background, the aim of the present study is to assess genetic pleiotropy related to the serotonergic system (SLC6A4, 5HTR2A, 5HTR2C, TPH2, SLC18A1), in a common phenotype such as very-early age of onset. One hundred and sixteen adolescents diagnosed with AN and 74 adolescents diagnosed with OCD participated in the present study. We confirmed the existence of a genetic overlap between OCD and AN. Specifically, we described genetic pleiotropy for age at onset across these disorders, associating two SNPs (rs6311, rs4942587) of the HTR2A with the very-early onset phenotype.